The role of n-3 polyunsaturated fatty acids in brain: Modulation of rat brain gene expression by dietary n-3 fatty acids - Kitajka, Klára (The National Academy of Sciences, 2002)
Rats were fed either a high linolenic acid (perilla oil) or high eicosapentaenoic + docosahexaenoic acid (fish oil) diet (8%), and the fatty acid and molecular species composition of ethanolamine phosphoglycerides was determined. Gene expression pattern resulting from the feeding of n-3 fatty acids also was studied. Perilla oil feeding, in contrast to fish oil feeding, was not reflected in total fatty acid composition of ethanolamine phosphoglycerides. Levels of the alkenylacyl subclass of ethanolamine phosphoglycerides increased in response to feeding. Similarly, levels of diacyl phosphatidylethanolamine molecular species containing docosahexaenoic acid (18:0/22:6) were higher in perilla-fed or fish oil-fed rat brains whereas those in ethanolamine plasmalogens remained unchanged. Because plasmalogen levels in the brains of rats fed a n-3 fatty acid-enriched diet increased, it is plausible, however, that docosahexaenoic acid taken up from the food or formed from linolenic acid was deposited in this phospholipid subclass. Using cDNA microarrays, 55 genes were found to be overexpressed and 47 were suppressed relative to controls by both dietary regimens. The altered genes included those controlling synaptic plasticity, cytosceleton and membrane association, signal transduction, ion channel formation, energy metabolism, and regulatory proteins. This effect seems to be independent of the chain length of fatty acids, but the n-3 structure appears to be important. Because n-3 polyunsaturated fatty acids have been shown to play an important role in maintaining normal mental functions and docosahexaenoic acid-containing ethanolamine phosphoglyceride (18:0/22:6) molecular species accumulated in response to n-3 fatty acid feeding, a casual relationship between the two events can be surmised.